Accelerated cluster dissolution using electropulsing for ultrafast performance regeneration. (15th March 2020) - Qin, Shuyang; Ba, Xin; Zhang, Xinfang
Abstract: Precipitation of copper-rich nanoclusters is the chief culprit, which is the cause of embrittlement of reactor pressure vessels. Here we provide a real sense of ``in situ'' pathway to investigate ultrafast performance regeneration under electropulsing. We find that the pulsed electric current can reduce the dissolution temperature of nanoclusters. The number of nanoclusters can be decreased drastically at relatively low temperature (430 °C), and the process takes only 3 min. Meanwhile, the toughness recovered more than 70%. The homogenization annealing treatment without pulsed electric current (430 °C/3 min) shows that the microstructure and mechanical properties do not change substantially. Graphical abstract: Image, graphical abstract